Quantifying redox metabolism in the plant metabolic network - Smith, E (2021)
The aim of this thesis was to develop and evaluate methods for quantifying redox metabolism in plants. Current methods suffer from a lack of: quantitative measurement; specificity between different redox carriers; and subcellular resolution. Three approaches were explored to address these limitations including, deuterium labelling, genetically encoded fluorescent biosensors for redox metabolites, and isotopically non-stationary metabolic flux analysis (INST-MFA). Deuterium labelling strategies for quantifying NADPH production fluxes were found to be ineffective in plants due to hydrogen exchange between NADPH and water, catalysed by flavin-enzymes. Fluorescent biosensors were effective at quantifying changes in NADH:NAD+ ratios and NADPH concentrations in Arabidopsis leaves, and identified dynamic responses to pathogen elicitation, hypoxia, nitrogen supply and menadione treatment. INST-MFA using [13C]glucose was used to quantify changes in subcellular fluxes of heterotrophic Arabidopsis cells under menadione induced oxidative stress; major changes in flux through anaplerotic reactions were identified and coenzyme balancing suggested the majority of biosynthetic NADPH demand could be met by isocitrate dehydrogenase. Of the methods evaluated, INST-MFA has the potential to make the largest contribution to quantifying redox metabolism in plants by providing measurement of specific subcellular fluxes, although this approach remains limited by a lack of coenzyme specificity. Further development of fluorescent biosensors to allow quantitative calibration will provide critical information for kinetic or thermodynamic models of plant metabolism. The methods developed in this thesis provide a set of tools for quantifying redox metabolism in plants that can be applied to improve our fundamental understanding of plant biology and meet biotechnological aims.